INFLUENCE OF ONLINE GAMES ON ACADEMIC ACHIEVEMENT WITH LEARNING MOTIVATION AS A VARIABLE OF MODERATION (CASE STUDY AT 6TH CITY BENGKULU STATE HIGH SCHOOL). - Mayang Sari; Dodo Sutardi; Evsa Wulan Suri (Yayasan Wayan Marwan Pulungan, 2024)
The objective of this study is to find out the influence of online gaming on academic achievement. To find out how learning motivation affects academic accomplishment. To learn about the impact of learning motivations as a variable of moderation on the relationship between playing online games and academic performance. The research aims to verify the influence of variables using statistical methods, in other words, this research according to the type of data used is quantitative. The selection and use of quantitative research designs in this study are to analyze factors in a variety of online games that influence learning motivation as a moderation variable. The results of the descriptive analysis obtained that the online game variable (Variable X) consists of statements related to indicators of involvement in online game games, betting on time playing online games, online game addiction, and the negative impact of playing online games did not affect lowered academic performance of respondents/students at State High School 6 Bengkulu in strengthening with the value of the influence of the online gaming variable on academic achievement of 16.3%. The result of the R2 test was a score of 0.163, so it can be concluded that the magnitude of the influence of the online game variable on academic achievement with learning motivation as the moderation variable is 0.163 or 16.3%, the rest of the academic performance is influenced by other factors outside the study.